Improved Tear Film Stability in Patients with Dry Eye After Hyaluronic Acid and Galactoxyloglucan Use - Molina-Solana P (Dove Medical Press, 2020)
Pedro Molina-Solana,1 Francisco de Borja Domínguez-Serrano,1 Antonio Manuel Garrido-Hermosilla,1,2 Jesús Montero-Iruzubieta,1,2 Ana Fernández-Palacín,3 Enrique Rodríguez-de-la-Rúa-Franch,1,2 Manuel Caro-Magdaleno1,2 1Ophthalmology, Virgen Macarena Hospital Seville, Seville, Spain; 2Surgery Department, University of Seville, Seville, Spain; 3Preventive Medicine and Public Health Department, University of Seville, Seville, SpainCorrespondence: Manuel Caro-Magdaleno Calle Bogotá 7, Bloque 3, 1ºB, Seville 41013, SpainTel +34 609030403Email mcaro79@gmail.comPurpose: Artificial tears only provide transient relief for dry eye. To the best of our knowledge, this is the first study to objectively compare treatment with artificial tears with Keratograph 5M, which allows accurate and objective investigation of dry eye and artificial tear treatment. We aimed to evaluate whether a preservative-free combination of 0.4% hyaluronic acid and 0.2% galactoxyloglucan can improve dry eye using the new topographer, Keratograph 5M.Patients and Methods: This prospective longitudinal, single-arm interventional cohort study was performed at a tertiary referral center and involved 20 patients with dry eye (40 eyes). Preservative-free artificial tears were administered every 3 h. The participants underwent clinical and instrumental evaluations at baseline, 15, 30, 60, 90 and 120 min after instillation and 1 week and 1 month after treatment. Baseline values were considered as the controls. All patients were assessed with Keratograph 5M for non-invasive Keratograph first break-up time and non-invasive Keratograph average break-up time, conjunctival hyperemia, and tear meniscus height. Ocular surface staining with fluorescein was evaluated using the slit-lamp and fluorescein break-up time examinations, and the Ocular Surface Disease Index score was recorded for each patient.Results: The signs and symptoms improved after 1 month of preservative-free 0.4% hyaluronic acid and 0.2% galactoxyloglucan treatment. There was a significant increase in the non-invasive Keratograph first break-up time and non-invasive Keratograph average break-up time at 15, 30, 60, and 90 min, and 1 week and 1 month (P < 0.05) and a decrease in hyperemia, corneal staining, and Ocular Surface Disease Index scores after 1 week and 1 month (P < 0.05). No treatment-related adverse event was observed.Conclusion: A combination of 0.4% hyaluronic acid and 0.2% galactoxyloglucan artificial tears seems effective for treating dry eye. Keratograph 5M can objectively detect these changes during the follow-up period.Keywords: artificial tears, Keratograph, non-invasive Keratograph break-up time, Ocular Surface Disease Index, dry eye